ANALYZING LEARNERS’ IDENTITY AND DIFFERENCE THROUGH ENGLISH MEETING CLUB - Suharti Sirajuddin; muhammad Yahrif (Universitas Islam Negeri Alauddin Makassar, 2020)
The article aims at finding out students’ learner identity and difference through English Club Meeting at Megarezky Universitas. This research investigated twenty members of English Club Meeting of Megarezky University (E-Comers) who come regularly and five respondents for interview. The method of this research is used observation, field note, and interview. The data collecting were analyzed by presented, analyzed, discussed and interpreted. The result of this research categorized four factors in order to understand learner identity, motivation, learning strategies, learner autonomy, and cross linguistic influence. In motivation, students are motivated due to the value of group community, students’ personal goal, and senior members’ role. While in learning strategies; coping and communication strategies are appeared on this research. Talking about learner autonomy, it is revealed that students’ control is the most effective strategies. So, it can be concluded that cross-linguistic influences students in English learning process. In conclusion, these four factors help teachers to understand students’ identity and difference. Every student has different motivation, learning strategies, students’ autonomy and cross-linguistic influence factors which English Meeting Club tends to accommodate students’ identity in one group activity.